Larangan Begadang sebagai Pemeliharaan Imunitas Perspektif Islam - Almunawir, Nurip (Jurnal Riset Agama, 2022)
This study intends to analyze the hadith about the prohibition of staying up late as immunity maintenance. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods by applying contemporary analysis in the medical field. The results of the research and discussion show that the hadith regarding the prohibition of staying up late is of authentic quality based on the takhrij review so that it can be accepted as an Islamic argument. As for the syarah of this hadith, it shows that staying up late is a behavior that the Messenger of Allah hated, the attitude of the Apostle can be understood, that he forbade his people to stay up late, while this prohibition is only makruh and not haram. The conclusion in this study is that the hadith narrated by Imam Ahmad no. 18945 is maqbul for efforts to increase immunity by prohibiting staying up late.